The Social Market Economy and Restriction of Free Movement Rights: plus c'est la même chose?. (29th November 2018) - Nic Shuibhne, Niamh
Abstract: Case law restricting free movement rights is criticized for privileging the internal market over social rights, achieved through reductive 'binary' reasoning that focuses too narrowly on the 'free movement versus social rights' dimension of the conflict. The problem is typically discussed for the economic freedoms but is evident elsewhere in free movement law too. This point is demonstrated through the example of EU citizenship and social assistance, which establishes that protecting national public finances justifies free movement restrictions when citizens are not seen as market participants. For better integration of economic, social and constitutional objectives, judicial assessments have progressed in some respects beyond the binary conflict method, evidencing the beginnings of the more complex accommodation of multiple dimensions that a system of multilevel constitutionalism requires. However, these advances have not yet produced significantly different outcomes in practice. The legacy of binary conflict reasoning proves stubbornly resilient to change.